Pemikiran Al-Kindi (Rasional-Religius) Tentang Pendidikan Islam Dan Relevansinya Terhadap Pendidikan Islam Kontemporer - Nurul Islam (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
The purpose of this study is to find out how Al-Kindi's biography, his works, his thoughts, and the relevance of his thoughts to contemporary Islamic education. In this study the authors used qualitative research through a library research approach, namely research conducted by collecting information and data through the help of various materials in the library such as reference books, similar previous research results, articles, and various journals. related to the problem to be disclosed. In this study, one primary source was used, namely a book written by George N. Atiyeh entitled Al-Kindi: The Philosopher Of The Arabs, translated by Kasidjo Djojosuwarno. While secondary sources are from 20 books and 11 scientific journals related to Al-Kindi's thoughts. This study analyzes Al-Kindi's thoughts about God, religion and philosophy, soul and reason, then these thoughts are analyzed to find their relevance in contemporary Islamic education. The results of this study indicate that the relevance of Al-Kindi's thoughts to contemporary Islamic education can be seen from the formulation of curriculum or Islamic education materials that are in line with Al-Kindi's divine thoughts, the 21st century learning contained in KMA no. 183 is in line with his thoughts on philosophy and religion, goals Islamic education is in line with his thoughts about the soul, and the competency standard qualifications of graduates are in line with his thoughts about reason.